Model Pemilihan Pemasok Bahan Baku Kelapa Parut Kering dengan Metode AHP (Studi Kasus PT. Kokonako Indonesia) - Siti Wardah (Jurnal Optimasi Sistem Industri, 2013)
The selection of suppliers is a strategic activity, especially if the supplier will supply critical items and/ or will be used in the long term. Many factors need to be considered in the selection of suppliers. PT. Kokonako Indonesia is one of the companies of the Group are located in Medan Capella. There are weaknesses in the selection of suppliers conducted by PT. Indonesia Kokonako the decision maker for the purchase of raw materials which are not within specification diameter ≥ 10 cm. Therefore, this study aims to perform the selection of suppliers with the consideration of a more comprehensive and objective as needed. The first stage is carried out in order to represent the actual circumstances is to identify the criteria, sub-criteria, and alternatives that will be used in the selection of suppliers. There are 6 criteria, 13 subcriteria, and 4 alternatives used in the selection of suppliers for raw materials dried grated coconut. The second stage, the stage determines the method for the selection of suppliers. Based on the identification there are no dependencies between sub criteria. Therefore, the exact method used to determine the priority of suppliers to be selected is the method of analytical hierarchy process (AHP). By using the AHP, the priorities selected suppliers for raw materials are dried grated coconut and weighs 0.363 Tempuling District as a top priority. Followed by Sub Tembilahan with weights 0.268, third priority is the District Enoch with weights 0.213, and the last is the Sub Trunk Tuaka and weighs 0,157.